Variable Voltage-based Power Management of DC Microgrids : With Focus on Shipboard Power Systems - Alho, Timo M. R. (Vaasan yliopisto, 2025)
For over a century, AC power distribution as proven technology has been the standard in shipboard power systems. However, increasing demands for fuel efficiency and emissions reduction are driving a shift toward DC distribution, enabled by power electronics-based technology. DC microgrids allow more efficient integration of variable-speed generators, energy storage, and renewables, but conventional control strategies remain based on AC-distribution's principles, prioritizing rigid voltage regulation over system flexibility and resilience. This dissertation proposes a variable voltage-based control strategy for DC microgrids, enhancing fault resilience and autonomous power management in shipboard power systems. Unlike conventional methods that rely on centralized control, the proposed strategy leverages natural voltage variations, allowing distributed, self-regulating operation. Modern load inverters, traditionally passive in voltage control, actively contribute to grid stabilization through their undervoltage and overvoltage regulators, enabling loads to support voltage sources when needed. This prevents overloading and black-outs without requiring a supervisory system. Key contributions of the research include: (1) the development of a mathematical modeling paradigm accurately representing the behavior of DC microgrids, including load inverter voltage regulators; (2) new load inverter under- and overvoltage regulator algorithms enabling smooth parallel operation with other voltage-maintaining equipment; (3) new energy storage state-of-charge balancing algorithms compatible with the control strategy, ensuring stable voltage levels; and (4) a detailed performance evaluation of the strategy in shipboard scenarios, including case studies on power supply prioritization and blackout prevention using real-world data. Modeling results and real-world validations demonstrate that the proposed control strategy significantly improves the resilience, efficiency, and fault tolerance of DC microgrids in marine applications. The findings suggest that this approach can serve as a robust alternative to conventional centralized power management systems, offering a scalable and autonomous solution for next-generation shipboard power systems.

Yli vuosisadan ajan AC-sähkönjakelu on ollut laivojen sähköjärjestelmien vakiintunut standardi. Kasvavat vaatimukset polttoainetehokkuudelle ja päästövähennyksille ohjaavat kuitenkin kehitystä kohti tehoelektroniikkaan perustuvaa DC-jakelua. DC-mikroverkot mahdollistavat säädettävänopeuksisten generaattoreiden, energian varastoinnin ja uusiutuvien energialähteiden tehokkaamman integroinnin, mutta perinteiset ohjausstrategiat pohjautuvat AC-jakelun periaatteisiin, keskittyen jäykkään jännitteen säätelyyn järjestelmän joustavuuden ja vikasietoisuuden kustannuksella. Tämä väitöskirja esittää vaihtelevaan jännitteeseen perustuvan tehon-hallintastrategian DC-mikroverkoille, parantaen vikasietoisuutta ja autonomista jännitteenhallintaa. Toisin kuin keskitetyt menetelmät, strategia hyödyntää DC-jännitteen luonnollista vaihtelua, mahdollistaen hajautetun ja itseohjautuvan toiminnan. Kuormainvertterit, jotka eivät perin-teisesti osallistu jännitteensäätöön, tukevat verkon vakautta ali- ja ylijännitesäätimiensä avulla. Tämä mahdollistaa kuormien itsenäisen tuen jännitelähteille, estäen lähteiden ylikuormitukset ja sähkökatkot. Tutkimuksen keskeiset kontribuutiot ovat: (1) matemaattinen mallinnus-paradigma, joka kuvaa DC-mikroverkon ja kuormainvertterien jännitesäätäjien toimintaa; (2) uudet ali- ja ylijännitesäädinalgoritmit, jotka mahdollistavat sujuvan rinnakkaistoiminnan muiden jännitettä ylläpitävien laitteiden kanssa; (3) uudet varaustilan tasapainotusalgoritmit energian varastoinnille, jotka toimivat yhteen ohjausstrategian kanssa ja takaavat häiriöttömän jännitetason; (4) strategian suorituskyvyn arviointi laivakäytössä, sisältäen tehonsyötön priorisointiin ja sähkökatkojen estämiseen liittyviä sovelluksia. Mallinnus- ja kenttätestitulokset osoittavat, että esitetty hallintastrategia parantaa selvästi DC-mikroverkkojen vikasietoisuutta, energiatehokkuutta ja luotettavuutta merisovelluksissa. Tulokset viittaavat siihen, että menetelmä voi toimia vahvana vaihtoehtona perinteisille keskitetyn hallinnan järjestelmille, tarjoten skaalautuvan ja autonomisen ratkaisun tulevaisuuden laivasähköjärjestelmille.
Keywords: electrical power networks; microgrids; distribution of electricity; fi=Sähkötekniikka|en=Electrical Engineering|